O koncepcji prawa socjalistycznego: [Concept of socialist law] (Studia Prawnicze / The Legal Studies, 1985)
On the basis of socialist legal order “expanded” concepts of law (e.g. law, legal norms and sense of law, legal norms and social relations; legal norms, social relations and sense of law, etc.) should be disregarded. The main disadventage of those concepts of law is that criteria of legality (illegality) of acts (decisions, actions) of state organs and other subjects may be freely established, thus citizens’ constitutional rights and freedoms may be restricted and some duties and obligations may be imposed on them. The concept of a “closed” system of law is deprived of those disadvantages. The concept is characterized by four basic features: 1) acts of standing of a law are at the top of legal norms hierarchy, 2) all other legislative acts should be proclaimed on the basis of powers provided for by the law and their scope should be in line with the law, 3) the mode of proclamation of legislative acts, especially of laws, it determined by legal norms of a given system, 4) it has been assumed that setting up law is separated from application of law.A legislative act is an act proclaimed by a state organ or another competent subject on the basis of powers provided for by the constitution or other law in a form provided for by the law and comprising norms which determine certain behaviour in the circumstances provided for in those norms (general and abstract norms).Two basic forms of creating socialist law may be distingushed: 1) proclaiming legal norms by means of unilateral legislative decisions (law, ordinance, resolution, etc.), and 2) agreement, i.e. proclaiming a norm of procedure by two or more subjects; the norm may provide for different behaviour of the partners.In the system of socialist law two types of legislative acts may be distinguished: 1) generally binding legislative acts, 2) legislative acts of internal management.The first type of acts is characterized by three features: a) a general character of norms of procedure concerning all categories of receivers, b) specified legal conditions of proclaiming legislative acts, c) an obligation of publication of a legislative act in accordance with the law.Legislative acts of the second type are also characterized by three features: a) regulation of behaviour of receivers inside a given organizational system of the state, b) dependence of a legislative act on legal provisions defining the organization and powers of a state organ, c) a lack of a general obligation of publication of the legislative act.